(untitled) (Bangladesh Journal of Medical Science, 2014)
This case report illustrates the management of a patient with Obsessive Compulsive Disorder who presented with hypochondriacal and persecutory ideas. Cognitive behavioural hypnotherapy approaches were applied in the management as the patient not keen for pharmacological treatment. Obsessive thoughts were managed via distraction technique, thought stopping and modified it to a more helpful compulsive behavior via direct suggestion during hypnotic state. The compulsive behavior was managed via hypno-behavioural approaches, reinforced by direct suggestion and pseudo-orientation in time. The Subjective Unit of Distress Scale (SUDS), Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) scales were used to measure the progress of anxiety and depressive symptoms. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18308 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.221-223